SOCIAL INNOVATIONS DESIGN – THE VIEWPOINTS OF TEACHERS, EXPERTS AND STUDENTS (Innovation in Woodworking Industry and Engineering design, 2026)
The current article represents a newly introduced model in the training practice of the “De-sign of Environment for Disabled People” study module, which is a part of the “Engineering design” (Interior and design of furniture) masters program in the University of Forestry.The main focus is on putting the students in a real situation, where they can meet specialists from the practice of the social activities and the final users of their future-to-be products – disadvantaged children or children with different kinds of disabilities. In this way the studying process is formed into something more: through stimulating the engineering projection in 3D, put in real time with added emotions.This method differs with its way of stimulating the strengths of the ones being trained and the dynamization of their active involvement in the learning process with independent and in-dividual sides.It also provokes the development of new ideas and shows a new way of learning and sup-porting the students as it expands their business operations and includes them in working directly with the final users of different statuses and needs.